Effect of Capacitor between Drain and Gate Terminals on Gate Magnetic Coupling Drive for Series-connected Power Semiconductor Devices - Urakabe, Takahiro; Ishii, Kazuki; Hagiwara, Makoto; Higaki, Yusuke; Itogawa, Yuki; 隆浩, 浦壁; 一輝, 石井; 萩原 誠; 優介, 檜垣; 祐樹, 糸川 (IEEJ JOURNAL OF INDUSTRY APPLICATIONS, 2025)
This study describes the experimental verification of series-connected power semiconductor devices and quantifies the voltage imbalance which occurs during the switching operation when the gate magnetic coupling and the addition of capacitor between drain and gate terminals methods are combined. Experiments using 3.3kV/750A SiC-MOSFET/SiC-SBD power modules showed the voltage imbalance evaluation originating from the difference in gate signal transmission and gate drive voltage for the conventional, magnetic coupling, capacitor addition methods and the two methods in combination. The combination of the two methods minimizes the voltage imbalance under these conditions. Moreover, the relationship between capacitance and switching losses is clarified.